2010
DOI: 10.1186/1745-6150-5-21
|View full text |Cite
|
Sign up to set email alerts
|

Selection in spatial stochastic models of cancer: Migration as a key modulator of fitness

Abstract: BackgroundWe study the selection dynamics in a heterogeneous spatial colony of cells. We use two spatial generalizations of the Moran process, which include cell divisions, death and migration. In the first model, migration is included explicitly as movement to a proximal location. In the second, migration is implicit, through the varied ability of cell types to place their offspring a distance away, in response to another cell's death.ResultsIn both models, we find that migration has a direct positive impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
46
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(53 citation statements)
references
References 45 publications
6
46
1
Order By: Relevance
“…This very simple and relatively abstract system is an important case study because it allows a rigorous mathematical description of the ways of evolution in the simple case. It turns out that the results allow understanding of several more complex and more biologically relevant scenarios, including the mutation dynamics in spatial and hierarchically organized cell populations (12)(13)(14)(15).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This very simple and relatively abstract system is an important case study because it allows a rigorous mathematical description of the ways of evolution in the simple case. It turns out that the results allow understanding of several more complex and more biologically relevant scenarios, including the mutation dynamics in spatial and hierarchically organized cell populations (12)(13)(14)(15).…”
Section: Resultsmentioning
confidence: 99%
“…Most tissue in the human body exhibits strong spatial structure; interestingly, our theory suggests that this can decrease the time until a certain number of mutations have accumulated in a cell, and this could reduce the time to cancer. At the same time, however, extensive cell migration occurs in many tissues, and migration has been shown to lead to similar properties as mass action (14). Also, it has recently been shown that a hierarchical organization of cell lineages can significantly reduce the rate of double-hit mutant generation (15).…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, our theory suggests that this can minimize the time until a certain number of mutations have accumulated in a cell, and this could reduce the time to cancer. At the same time, however, extensive cell migration occurs in many tissues, and migration has been shown to lead to similar properties as mass action [23]. In addition, it has recently been shown that a hierarchical organization of cell lineages can significantly reduce the rate of double-hit mutant generation [40].…”
Section: Somatic Evolution In Tissuementioning
confidence: 99%
“…In addition, from microscopic dynamics utilizing the excluded volume approach, non-linear diffusion equations with diffusion coefficients depending on cellular volume fraction to prevent the collapse of cellular density were obtained [20]. These versatile models have been applied for interpreting different aspects of cell physiology [20][21][22][23][24][25][26][27][28]. Thus, an extended CPM version provided a strong correlation of cell migration directionality with topological surrounding extracellular matrix (ECM) distribution and a biphasic dependence of migration on the matrix structure and stiffness, cell density, and adhesion [27].…”
Section: Introductionmentioning
confidence: 99%